The Political Economy of the US-China Cybersecurity Relations and Trade War Under the Trump Administration - Miftahul Huda; Faris Al - Fadhat (Journal of Islamic World and Politics, 2022)
This article examines the cybersecurity relations between China and the US under the Trump administration. It explores the changes in the US cybersecurity policy in 2019, where the US government took a protectionist approach to ban the operation of China’s software and hardware in the US, and how such a decision predisposes the trade war between the two countries, which President Trump previously started. Appling the political economy approach of the cybersecurity concept, this research argues that the protectionist cybersecurity policy by the Trump administration was driven by the US business interest followed by security concern to lead the global technological transformation, balance the international economy, and preserve the US citizen’s big data.  Such policy, nevertheless, has intensified the trade war between the US and China, specifically in the technology and big data sectors. This study contributes to the broader literature on cybersecurity that has been much discussed in recent years.